PENERAPAN PENDEKATAN KONTEKSTUAL MENGGUNAKAN MEDIA GAMBAR UNTUK MENINGKATKAN KETERAMPILAN MENULIS DESKRIPSI PADA SISWA KELAS II SEKOLAH DASAR - Darmatul Asma Toja (Program Studi PGSD Universitas Flores, 2020)
This research was conducted because it was found that there were problems in the Indonesian language subject for grade II students of Bhoanawa 2 Impres Elementary School which showed very low Indonesian learning outcomes. The formulations of the problems in this study are: 1) Does learning through a contextual approach by utilizing animal image media can improve writing writing skills ?; 2) Can a contextual approach using animal pictures media increase student activity? The data collection methods used were: observation, interview, test and documentation. The subjects in this study were all students in grade II of the Bhoanawa 2 Impres Elementary School, totaling 17 people. This type of research is Classroom Action Research. The results showed that the increase in writing skills in writing was 29%, or only 5 out of 17 students who were able to write well, which could achieve a greater value of 67. The results of cycle I increased to 47.05% (less) because of 17 students 8 students who managed to get a score above the value of the Minimum Completeness Criteria, and in cycle II an increase of 88.23% (very good), of the 17 students sampled there were 5 students in the very good category and 10 students in the good category.